Spatial Ability in Learning Mathematics: Systematic Literature Review (SLR) - Naufal, Nasrul; Juandi, Dadang (KnE Social Sciences, 2024)
Spatial ability plays a crucial role in the study of geometry. When related to the context of mathematics, especially geometry, it becomes apparent that having and developing spatial abilities is crucial. Academic achievement, particularly in understanding mathematics and geometry, was closely linked to spatial ability. The researcher conducted a study using the Systematic Literature Review (SLR) method to uncover the latest information on spatial ability in learning mathematics. Summarizing and interpreting a total of 18 accredited journal articles from various databases in the period 2016-2021, the researcher produced a review presented in a graph, including the year of publication, education level, a method used, sample size, and demography. Spatial abilities in mathematics learning have received considerable attention in research. However, the number of studies on spatial abilities in mathematics learning has decreased in the last two years. In addition, spatial abilities in early childhood have not been optimized. This is disappointing because spatial abilities are closely related to children’s cognitive development. This literature review recommends conducting research on spatial abilities in various provinces in Indonesia, emphasizing the significance of high spatial abilities for good mathematical performance. Keywords: learning mathematics, spatial ability, systematic literature review